Plan of the Tract of Land Purchased from the Mississauga Indians in 1806. - Ridout, Thomas (Surveyor)
Map shows the subdivisions and purchase of the Indian Reserve on the Credit River, 12 Mile, and 16 Mile Creek. While the purchase took place in 1806, this map was published by the Department of Indian Affairs in 1820. Rivers, creeks, and Lake Ontario are labelled. There is a large compass rose on the right of the map. Some large cities and towns are labelled. Text towards the bottom of the map describes the locations of Indian reserves. Scale: 1:158,400 [approx.] Legend, signed “Survey Gens. Office. York. 22nd Jany. 1820.” Legend lists the subdivisions of the Indian Reservation lands and the average. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .